Opinion of Healthcare Professionals in the Usage of Social Media for Patient Care in Majmaah, Saudi Arabia - Syed Meraj Ahmed; Faisal Alhumaidi Alruways; Thamer Fahad Alsallum; Meshal Munahi Almutairi; Abdullah Saif Al-Subhi; Ahmed Abdulaziz Ababdulkarim (International Journal of Public Health Science (IJPHS), 2017)
Use of social media for patient care is the new frontier in the healthcare indus-try. Sharing of information between the clinicians and their patients is now so much easier. In slowly gaining a foothold worldwide it needs a healthy push to make it universally accepta-ble. Study the knowledge, attitude, and practices of healthcare providers on the usage of social media in their clinical practice.A baseline cross–sectional study was conducted among 200 healthcare professionals from March 2015 to September 2015 on their knowledge, attitude, and practices in the use of social media for patient care in Majmaah, Saudi Arabia. A close ended self – administered validated questionnaire was used to gather data which was analyzed by using the SPSS ver. 21.0 software. 55.3% participants used social media for both professional and personal reasons. Some (25.3%) specified using it for patient care while a significant majority (52.9%) opined that it can be successfully used for patient interaction. Nearly 55% agreed that social media should not be banned due to its benefits as an efficient tool for patient communication. Social media use for pa-tient doctor interaction should be encouraged to improve patient care through effective communication.